MODEL PYROXENES I: IDEAL PYROXENE TOPOLOGIES - Thompson R.M.; Downs R.T. (My University, 2003)
Ideal pyroxenes are hypothetical structures based on ideal closest-packed arrangements of O anions. They are modeled after observed pyroxene structures and have the general formula M2M1T2O6, where M2 and M1 represent octahedrally coordinated cations, and T represents tetrahedrally coordinated cations. An algorithm has been created to construct all possible ideal pyroxenes based on closest-packed stacking sequences of length 12 or less. These structures are reported. The only significant structural parameters that vary between different ideal pyroxenes are the M1-T and M2-T distances. We show that the repulsive forces between these pairs of cations distinguishes the energetics of the ideal pyroxenes and may be important in determining the topologies of observed pyroxenes.
Keywords: MINERALOGY; ALGORITHMS; CRYSTALS; HYPOTHESES; pyroxenes